2015
DOI: 10.1016/j.psyneuen.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The cortisol awakening response (CAR) in toddlers: Nap-dependent effects on the diurnal secretory pattern

Abstract: INTRODUCTION Cortisol levels in adults show a sharp decrease from midmorning to midafternoon. Most toddlers take afternoon naps, which is associated with a less mature diurnal pattern characterized by a midday plateau in cortisol secretion. Napping in preschoolers produces a robust cortisol awakening response (CAR), which may account for such maturational differences. This experimental study extends prior work by examining whether the presence and timing of the nap-dependent CAR influences the diurnal cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…These cortisol increases were partly explained by the afternoon naps, as about 35% of the afternoon saliva samples were taken 15-60 min after waking up. This association between afternoon napping and the cortisol levels was expected, as napping has been found to result in a post-nap cortisol rise in toddlers [21]. Previous research studies have defined the cortisol awakening response (CAR), which describes the period of increased cortisol secretion approximately 30-45 min post-awakening [20].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…These cortisol increases were partly explained by the afternoon naps, as about 35% of the afternoon saliva samples were taken 15-60 min after waking up. This association between afternoon napping and the cortisol levels was expected, as napping has been found to result in a post-nap cortisol rise in toddlers [21]. Previous research studies have defined the cortisol awakening response (CAR), which describes the period of increased cortisol secretion approximately 30-45 min post-awakening [20].…”
Section: Discussionmentioning
confidence: 78%
“…Thus, cortisol secretion does not only follow the circadian rhythm but is also nap-dependent in toddlers. The pronounced cortisol rise is observed to follow both the morning and afternoon naps in comparison with the no-nap condition [21].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…By assessing nighttime along with daytime sleep–wake patterns, wake time and daytime napping have been demonstrated to induce modifications of CAR. 40 , 41 Previous studies have suggested that emergence of CAR varies by individual and can appear from 2 to 6 months of age. 10 , 11 Current study results confirm the presence of CAR by ~2 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that some younger children have a nap after childcare, resulting in an elevation of cortisol, which is called a cortisol awakening response (CAR) (Tervahartiala et al 2019). However, evening napping has been observed to not produce much cortisol (Tribble et al 2015). To alleviate tension, children might benefit from calm evenings with focused care from parents (Ahnert and Lamb 2003).…”
Section: Secondary Findings: Agementioning
confidence: 99%